Nike-s self-evident supremacy within rising competition. how to grow stronger in a post-endemic environment - Viana, Alexandra Leonor De Vasconcelos e (2022)
The purpose of this paper is to enlighten its readers on whether Nike will be able to maintain its leading position in the footwear and apparel markets. During the uncertain times we are living, it will be explored what Nike’s future strategies and expected outcomes are, that could allow it to prosper and further outpace its peers. The research is done by first approaching Nike’s current activities and future actions, and later by delving into the industry trends and opportunities that Nike could capture. A competitive analysis is performed to infer Nike’s current position and its financial strength is scrutinized to infer its sustainability. To finish, it will be presented several risks inherent to investing in Nike’s stock given the current economic and geopolitical context. All the analysis is done under the light of the recent Covid-19 pandemic, and ideas are shared on how to adjust to the new normal.